2014
DOI: 10.1007/s13187-014-0735-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perception of Information and Health-Related Quality of Life 1 Month After Discharge for Colorectal Cancer Surgery

Abstract: The aim of this study was to investigate how patients perceive information and their health-related quality of life 1 month after discharge for colorectal cancer surgery. The aim was also to compare these results with the first 2 weeks at home and to identify factors related to the perception of information. One hundred patients from three surgical clinics in the south of Sweden were included in this study. Perception of information was assessed with EORTC QLQ-INFO25, health-related quality of life with QLQ-C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Lithner et al. (, ) describe the discharge process as unstructured with mostly verbal information, and the patients as having not yet regained their capacity to assimilate information in an early post‐operative recovery state. Since most CRC wards deliver written information, albeit of varying quality and lacking in reader interaction and motivation (Smith et al., ), there might be a need for an approach where, before the operation, patients are encouraged to find and strengthen their capacities rather than just passively assimilate both oral and written information (Fraser & Greenhalgh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Lithner et al. (, ) describe the discharge process as unstructured with mostly verbal information, and the patients as having not yet regained their capacity to assimilate information in an early post‐operative recovery state. Since most CRC wards deliver written information, albeit of varying quality and lacking in reader interaction and motivation (Smith et al., ), there might be a need for an approach where, before the operation, patients are encouraged to find and strengthen their capacities rather than just passively assimilate both oral and written information (Fraser & Greenhalgh, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the enhanced recovery after surgery (ERAS) protocol has been positively evaluated and proven to be best evidence‐based practice during pre‐ and postoperative CRC care, reducing morbidity, mortality and length of stay in hospital. An essential part of the ERAS programme occurs in the preoperative context where the starting point is to give a structured information regarding all concepts included in the programme, for example nutrition, bowel function, mobilisation, so that the patient feel well informed, know what is expected and can actively participate in their own care . An important part of the protocol is to coach the patient throughout the hospital stay to improve recovery .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with colorectal cancer have been found to lack information on the disease and the treatment [3][4][5]. Patients with poorer physical status as indicated with a higher ASA score, and patients living without a partner, are less satisfied with the information received [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with colorectal cancer have been found to lack information on the disease and the treatment [3][4][5]. Patients with poorer physical status as indicated with a higher ASA score, and patients living without a partner, are less satisfied with the information received [3,6]. Preoperative information and education as a method of improving outcomes for treatment of colorectal cancer has seldom been studied, but one study of patients receiving a stoma concluded preoperative education was more effective than the traditional education given postoperative [7].…”
Section: Introductionmentioning
confidence: 99%